The Effectiveness of Telerehabilitation for Post Stroke Patients - Gabrielle Glenis; Regina Caecilia Setiawan; Tresia Fransiska Ulianna Tambunan (PT Kalbe Farma Tbk., 2021)
Stroke rehabilitation is an essential component of post-stroke care and is more effective if started sooner. Stroke rehabilitation therapy aims to improve motor function, psychological well-being, cognitively, emotionally, and in terms of social well-being. Telerehabilitation allows communication between medical staff and patients and can be a suitable alternative to usual rehabilitation care in poststroke patients. This method may have potential implications for patients, especially in remote or underserved areas. Future trials are needed on telerehabilitation’s feasibility, efficacy, and cost-effectiveness in other low and middle-income countries where the stroke burden is burgeoning. Rehabilitasi stroke merupakan komponen penting dalam tatalaksana pasca-stroke dan lebih efektif untuk dimulai lebih awal. Tujuan terapi rehabilitasi stroke adalah untuk meningkatkan fungsi motorik, kognitif, emosional, kesejahteraan psikologis dan sosial. Telerehabilitasi memungkinkan komunikasi antara staf medis dan pasien dan dapat sebagai alternatif yang sesuai untuk perawatan rehabilitasi biasa pada pasien pasca-stroke. Metode ini mungkin memiliki implikasi potensial bagi pasien, terutama di daerah terpencil atau kurang terlayani. Penelitian masih diperlukan untuk kelayakan, kemanjuran, dan keefektifan biaya telerehabilitasi di negara berpenghasilan rendah dan menengah dengan beban stroke meningkat.